2021
DOI: 10.2337/dc21-0878
|View full text |Cite
|
Sign up to set email alerts
|

Islet Autoantibody Type-Specific Titer Thresholds Improve Stratification of Risk of Progression to Type 1 Diabetes in Children

Abstract: OBJECTIVE To use islet autoantibody titers to improve the estimation of future type 1 diabetes risk in children. RESEARCH DESIGN AND METHODS Prospective cohort studies in Finland, Germany, Sweden, and the U.S. followed 24,662 children at increased genetic or familial risk to develop islet autoimmunity and diabetes. For 1,604 children with confirmed positivity, titers of autoantibodies against insulin (IAA), GAD antibodies (GA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The case children in this set included 54 children who developed IAA as the first appearing islet autoantibody (26% girls) and 57 children who developed GADA as the first‐appearing autoantibody (40.3% girls), representing the two main endotypes of T1D (IAA‐first or GADA‐first endotypes). Individuals testing positive for multiple autoantibodies are highly likely to progress to T1D 32–35 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case children in this set included 54 children who developed IAA as the first appearing islet autoantibody (26% girls) and 57 children who developed GADA as the first‐appearing autoantibody (40.3% girls), representing the two main endotypes of T1D (IAA‐first or GADA‐first endotypes). Individuals testing positive for multiple autoantibodies are highly likely to progress to T1D 32–35 …”
Section: Methodsmentioning
confidence: 99%
“…Individuals testing positive for multiple autoantibodies are highly likely to progress to T1D. [32][33][34][35] The age at seroconversion in the two endotypes was, as…”
Section: Hla Risk-matched Seriesmentioning
confidence: 99%
“…We and others have shown the value of IA-2A, HbA 1c and intermediate OGTT time points in stratifying risk in islet autoantibody-positive individuals who are genetically at risk for type 1 diabetes [23][24][25][26][27][28][29][30][31][32][33]. Some have developed scores that can stratify risk in relatives with either stage 1 or stage 2 type 1 diabetes [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The methods used by each study to measure IAA, GADA and IA-2A have been previously described [ 18 ]. Autoantibody levels for IAA, GADA, and IA-2A from the individual T1DI constituent studies were converted to multiples of the upper limit of normal (mULN) to facilitate comparisons, and were combined for analysis as previously described [ 17 ]. All mULN values, regardless of whether they were above or below the autoantibody positivity threshold, were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work [ 17 ], we harmonised IAb levels from our large, prospective Type 1 Diabetes Intelligence (T1DI) study cohort [ 18 ], identified the IAb type-specific titre thresholds (measured at the time of confirmed positivity) that maximised discrimination of 5-year type 1 diabetes risk, and used the thresholds to risk-stratify children in various age groups via survival analysis. This prior work demonstrated that IAb levels were useful in predicting type 1 diabetes onset, and motivated us to perform a more comprehensive assessment of the utility of measurement of IAb levels.…”
Section: Introductionmentioning
confidence: 99%